Pulsatilla chinensis extract alleviate Staphylococcus aureus induced mastitis in mice by regulating the inflammatory response and gut microbiota - Xiang, Yifei; Li, Ziyang; Liu, Chengzhi; Wei, Zhifei; Mo, Xuelian; Zhong, Yawen; He, Ruini; Liang, Zhengmin; He, Yucheng; He, Jiakang (Frontiers in Veterinary Science, 2025)
IntroductionSubclinical mastitis (SCM) caused by Staphylococcus aureus (S. aureus) is widely prevalent in cattle herds around the world, causing huge losses to the dairy cattle farming industry and dairy product production. Currently, the use of hormones and antibacterial drugs is the most effective treatment method. However, issues such as the increase in drug resistance and residues in dairy products limit their further application. In this study, based on the response surface optimization method, Pulsatilla chinensis extract (PCE) was prepared from Pulsatilla chinensis using ethanol as the medium in a simple, efficient and low-cost way. Its functions were verified both in vitro and in vivo.Methods and resultsThrough the Oxford cup method, MIC/MBC and co-culture experiments, it was demonstrated that PCE had a good inhibitory effect on the proliferation of four strains of S. aureusin vitro. The in vivo toxicity evaluation proved that PCE had high oral safety. In addition, we screened and established a mastitis model platform for lactating mice to evaluate the expected in vivo effects of PCE. The results showed that pre-treatment with PCE for 7 days significantly reduced the bacterial load and the levels of inflammatory factors (IL-6, IL-1β, TNF-α, MPO) in the mammary gland and blood induced by S. aureus, improved the pathological damage of the mammary gland tissue, and alleviated the occurrence of mastitis in mice by regulating the intestinal microbiota.ConclusionThese results verify that PCE can be used to treat mastitis caused by S. aureus, and thus it is expected to become an excellent alternative to hormones and antibacterial drugs.